Ansiedade e desempenho: uma análise experimental - Silva, Regina Celia Porto da (1983)
Anxiety is one of the most important concepts in Psychology. A great deal of experimental work, dealing with the test anxiety effects, has been undertaken. Discussion of test anxiety and its relation to academic performance must be preceded by an elucidation of the concept of anxiety. However this concept has been interpreted in different ways, by the various schools of thought in Psychology and Philosophy. The two first chapters of this work are devoted to a systematic presentation of the various concepts of anxiety and the theories which are considered the most important. This is followed by a description of an experimental analysis which was carried out with the double objective of detecting the test anxiety effects on performance and to verify the results of the manipulation of variable limited time and the stress magnitude in the connection learned. A good deal of work on anxiety has emphasized the complexity of its influence on behaviour. This research is based on Spielberger's work, which focuses the relationship between the student's performance and his level of anxiety. As in Spielberger's studies, we consider to be necessary to control the two variables: task difficulty and the intelligence of the subjects. Based on these results, we conclude that a series of other aspects must be considered, such as the elaboration of the quiz, the involved matter, the previous students' experience, the teacher's image etc. Knowledge of the nature of test anxiety and of effective ways to control this specific type of anxiety, would provide a way of helping the pupils to deal with it. It is also necessary for educators to know the characteristics and implications of test anxiety, in such a way as to be able to overcome and minimize its negative effects on the process of teaching and learning.